Regulatory T‐cell development and function are impaired in mice lacking membrane expression of full length intercellular adhesion molecule‐1. Issue 4 (28th October 2015) - Gottrand, Gaëlle; Courau, Tristan; Thomas‐Vaslin, Véronique; Prevel, Nicolas; Vazquez, Thomas; Ruocco, Maria Grazia; Lambrecht, Benedicte; Bellier, Bertrand; Colombo, Bruno M.; Klatzmann, David
Summary: To further investigate the contribution of intercellular adhesion molecule‐1 (ICAM‐1) to adaptive immune responses, we analysed T‐cell development and function in mice lacking full‐length ICAM‐1 (ICAM‐1 tm1Jcgr ). Compared with wild‐type (ICAM‐1 WT ) mice, ICAM‐1 tm1Jcgr mice have impaired thymocyte development. Proportions and numbers of double negative, double positive, mature CD4 + and CD8 + thymocytes, as well as of regulatory T (Treg) cells were also significantly decreased. In the periphery, ICAM‐1 tm1Jcgr mice had significantly decreased proportions and numbers of naive and activated/memory CD4 + and CD8 + T cells, as well as of Treg cells, in lymph nodes but not in the spleen. In vitro activation of CD4 + and CD8 + T cells from ICAM‐1 tm1Jcgr mice with anti‐CD3 antibodies and antigen‐presenting cells (APCs) resulted in a significantly weaker proliferation, whereas proliferation induced with anti‐CD3 and anti‐CD28 antibody‐coated beads was normal. In vivo immunization of ICAM‐1 tm1Jcgr mice resulted in normal generation of specific effector and memory immune responses that protect against a viral challenge. However, contrary to ICAM‐1 WT mice, immunization‐induced specific effectors could not eradicate immunogen‐expressing tumours. Treg cells from ICAM‐1 tm1Jcgr mice have abnormal activation and proliferation induced by anti‐CD3 antibody and APCs, and have markedly decreased suppressive activity in vitro . In contrast to ICAM‐1 WT mice, they were unable to control experimentally induced colitis in vivo . Hence, our results further highlight the pleiotropic role of ICAM‐1 in T‐cell‐dependent immune responses, with a major role in Treg cell development and suppressive function.